2015
DOI: 10.1016/j.envres.2014.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to extreme heat by socio-demographic characteristics and area green space among the elderly in Michigan, 1990–2007

Abstract: Objectives We examined how individual and area socio-demographic characteristics independently modified the extreme heat (EH)-mortality association among elderly residents of 8 Michigan cities, May-September, 1990-2007. Methods In a time-stratified case-crossover design, we regressed cause-specific mortality against EH (indicator for 4-day mean, minimum, maximum or apparent temperature above 97th or 99th percentiles). We examined effect modification with interactions between EH and personal marital status, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(106 citation statements)
references
References 32 publications
5
89
1
2
Order By: Relevance
“…However, non-green space was not a modifier in any model at any lag in our study. This is inconsistent with other studies which found differential vulnerability to heat-associated mortality in Michigan, Phoenix, Arizona and Barcelona, Spain by perception of green space, vegetation or imperviousness, even with control for other socioeconomic characteristics (Gronlund et al 2015, Harlan et al 2013, Xu et al 2013), although in Barcelona, the measured, as opposed to perceived, tree cover in a census tract was not a significant modifier. Uejio and colleagues (2011) also found imperviousness in a census block group (smaller than a ZIP code) to predict heat distress ambulance calls in Phoenix, Arizona but not heat-related mortality in Philadelphia, Pennsylvania.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, non-green space was not a modifier in any model at any lag in our study. This is inconsistent with other studies which found differential vulnerability to heat-associated mortality in Michigan, Phoenix, Arizona and Barcelona, Spain by perception of green space, vegetation or imperviousness, even with control for other socioeconomic characteristics (Gronlund et al 2015, Harlan et al 2013, Xu et al 2013), although in Barcelona, the measured, as opposed to perceived, tree cover in a census tract was not a significant modifier. Uejio and colleagues (2011) also found imperviousness in a census block group (smaller than a ZIP code) to predict heat distress ambulance calls in Phoenix, Arizona but not heat-related mortality in Philadelphia, Pennsylvania.…”
Section: Discussioncontrasting
confidence: 99%
“…We included interactions between each of the potential modifiers and both of the EH time lags to provide for either potential differences in vulnerability by lag or potential short-term declines in hospitalizations in the 2–5 days following EH within each category of modifier. In addition to parameters for each matched set of case and controls which were conditioned out of the likelihood function, we modeled: logitfalse(hospital0.16667emadmissionfalse)=β1MH01+β2MH25+β3EH01+β4EH25+β5EH01×EM1+β6EH25×EM1++β21EH01×EM8+β22EH25×EM8 where EM 1 –EM 3 were indicator variables Male, Black and Aged 78+, respectively, and EM 4 –EM 8 were ZIP-code “% Non-Green,” “% No HS,” “% Black” and “% Built < 1940,” respectively, modeled simultaneously (Gronlund et al 2015). We also considered models with “% Poverty” instead of “% No HS” as the measure of socioeconomic status.…”
Section: Methodsmentioning
confidence: 99%
“…These results are somewhat consistent with those of other, comparable studies (Gronlund et al 2015; Hondula et al 2015; Smargiassi et al 2009). For example, Hondula et al (2015) used baseline mortality at 10°C and observed mortality on hot days to report a 0–10% increase in risk for areas with temperatures > 30°C in multiple U.S. cities.…”
Section: Discussionsupporting
confidence: 93%
“…In comparison, locations between 20°C and 30°C had increases in risk ranging from –2.5% to 2.5%. In another spatially stratified case-crossover analysis of social vulnerability, Gronlund et al (2015) reported no significant differences in ORs for cardiovascular or respiratory mortality between all cases and those cases that occurred in areas of Michigan presumed to be vulnerable. The one exception was for respiratory mortality in areas with older housing.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation